Foreword - Editorial board (Ex Novo: Journal of Archaeology, 2021)
Making Archaeology Public. A View from the Mediterranean, Eastern Europe and Beyond The concept of Public Archaeology has profoundly changed since Mc Grimsey’s first formulation in the early 1970s, as it developed a solid conceptual and practical framework along the years that makes it now an independent branch of archaeology. However, in English-speaking and Northern European countries, the perception of archaeology as a common good was widely spread even before the actual formalization of Public Archaeology as a specific curriculum offered by several universities. Not surprisingly, such an earlier interest led to the development of a markedly North Europe-centric perspective on the topic, which keeps steering much of the current reflection on Public Archaeology despite the emergence of multiple and alternative standpoints on the matter, further deepening the great divide between the archaeologies of Northern and Southern European countries.